Crystal method. - Stevenson, R.
The author discusses a potential method for commercial production of GaN substrates, developed by a UK company, NanoGaN. Their nanocolumn growth technique is used to grow high-quality nanosized gallium nitride wafers on sapphire substrate. This method is based on the vapour deposition of GaN thin film on substrate, forming an array of nanometer-size holes in the surface of gallium, then producing gallium nitride layer by layer. The described approach can produce high quality GaN crystals with very few defects.
Keywords: Al2O3.; GaN; NanoGaN; Crystal defects; Crystal method; High quality gallium nitride crystals; Nanometer-size holes; Nanosized wafer growth; Sapphire substrate; Thin film deposition; Vapour deposition